Transformational Leadership on Affective Commitment with Trust in Leaders as a mediating variable at the Mentawai Islands District Attorney's Office - Dian Safitri; Mega Asri Zona (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze: (1) The effect of transformational leadership on the affective commitment of the Mentawai Islands prosecutor's office employees. (2) The effect of transformational leadership on trust in the leaders of the Mentawai Islands prosecutor's office. (3) The influence of trust in leaders on the affective commitment of the Mentawai Islands prosecutor's office employees. (4) Transformational leadership mediates trust in the leader towards the affective commitment of the Mentawai Islands Prosecutor's Office employees. The population in this study were all civil servants (PNS) at the Mentawai Islands Prosecutor's Office, totaling 30 Everyone. Sampling technique is performed using total sample where the number of samples is the same as the population totalling 30 people. Data collection by questionnaire with Likert scale. The results of this study indicate that: (1) transformational leadership has a positive and significant effect on the emotional commitment of the Mentawai Islands State Attorney's Office. (2) Some transformational leadership is positive and important effect on trust for the head of the Mentawai Islands State Attorney's Office. (3) trust in the leader has a positive and significant effect on emotional commitment of the Mentawai Islands floor (4) transformational leadership Has a positive and important effect emotional commitment with trust in the leader as a mediatorin the Mentawai Island Banquet